RENAISSANCE HEROES AND THEIR INFLUENCE ON THE DEVELOPMENT OF EMOTIONAL MATURITY IN ADOLESCENTS: INTERPRETATION OF SHAKESPEARE IN A MODERN CONTEXT - Jalolidin Zaynobidinov; Kambarova Saida Umaralievna (Bright Mind Publishing, 2026)
This article examines the influence of the heroes of Renaissance literature, and more specifically the heroes of the famous works of William Shakespeare, on the process of developing the emotional connection of adolescents between personality and hero. The article presents an analysis conducted with students aged 18 to 20 years, the main purpose of the test is to analyze the function of Identification of students with the images of outstanding heroes and assess their role as the main component of the development of personal qualities such as: love, devotion, dedication and honesty. As a result of the work, an anonymous online survey was conducted among adolescent and young adult students, as a test in the Telegram messenger, the total number of respondents was 22.
Keywords: Renaissance, William Shakespeare, heroes, identifications, formation of emotions, maturity, interpretation, literary influence, self-determination